1994
DOI: 10.1590/s0103-84781994000300001
|View full text |Cite
|
Sign up to set email alerts
|

Controle De Plantas Daninhas E Seletividade De Herbicidas Em Alho

Abstract: Foi conduzido um experimento de campo no município de Rio Grande, RS, na safra agrícola 1987/88, com objetivo de avaliar a eficiência de herbicidas no controle de plantas daninhas na cultura do alho, cultivar Quitéria. O delineamento experimental utilizado foi blocos ao acaso, com quatro repetições e os tratamentos constituídos pela aplicação de herbicidas em pré e pós-emergência, das plantas daninhas. Destas, as espécies predominantes na área experimental foram: Digitaria sanguinalis (L.) Scop., Eleusine indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…As a result of the low competitive capacity of garlic, it is common to have a reduced crop productivity due to weed interference, reaching up to 80% (Garcia et al, 1994), in addition to resulting in a long critical interference prevention period (CIPP), which generally ranges from 25 to 120 days after emergence for the cultivars used in Santa Catarina (Lucini, 2009). Studies by Contieiro et al (2008) found that for the garlic crop to express maximum productivity, the crop must be free of weeds from 20 to 100 days after planting the bulbils.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the low competitive capacity of garlic, it is common to have a reduced crop productivity due to weed interference, reaching up to 80% (Garcia et al, 1994), in addition to resulting in a long critical interference prevention period (CIPP), which generally ranges from 25 to 120 days after emergence for the cultivars used in Santa Catarina (Lucini, 2009). Studies by Contieiro et al (2008) found that for the garlic crop to express maximum productivity, the crop must be free of weeds from 20 to 100 days after planting the bulbils.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda que o oxyfluorfen não seja recomendado para a cultura do alho, alguns estudos tem demostrado eficácia de controle, quando esse herbicida é posicionado em PRÉ da cultura. Uma pesquisa em campo foi realizada no município de Rio Grande, localizado no estado do Rio Grande do Sul-RS, com objetivo de avaliar a eficácia de herbicidas no controle de plantas daninhas na cultura do alho cultivar Quitéria (GARCIA et al,1994). As espécies dominantes na área foram Digitaria sanguinalis, Eleusine indica, Spergula arvensis, Bidens pilosa.…”
Section: Propriedades Valoresunclassified